Generalized tanh method extended with the Riccati equation for solving the some of nonlinear equations - Körpinar, Zeliha Sariateş; Tuz, Münevver (My University, 2013)
In this paper, we find new exact traveling wave solutions of the Benjamin-Bona-Mahony equation, Lax's fifth-order KdV equation and Drinfeld-Sokolov-Wilson equation system by using generalized tanh method. The main idea of this method is to take full advantage of the Riccati equation which has more new solutions.
Keywords: Benjamin-Bona-Mahony equation; Drinfeld-Sokolov-Wilson equation system; Generalized tanh function method; Lax's fifth-order KDV equation; Riccati equation; Travelling wave solution